August Tobler, the Swiss Pioneer of South Sumatra Geological Mapping, 1900-1912 - J.T. (Han) van Gorsel; Bernhard Gunzenhauser (Ikatan Ahli Geologi Indonesia, 2021)
Dr. August Tobler was a well-known Swiss geologist, who, as one of the very first petroleum field geologists in the Netherlands Indies, did more than ten years of geological mapping in the tiger-infested jungles of South Sumatra. He first worked for the Koninklijke/Royal Dutch and Moeara Enim oil companies in South Sumatra from 1900 to 1904. This was followed by six more years of geological mapping in the Jambi basin, as the first non-Dutch geoscientist at the Dienst van het Mijnwezen (Geological Survey). His thoroughly documented monographs and geologic maps of his geological fieldwork in the Palembang and Jambi basins of South Sumatra, as well as the adjacent Barisan Mountains, set new standards for quality and detail.Much of the personal information on Dr. Tobler is from papers by Kugler (1930, 1963), Oppenoorth (1930), Stehlin (1931) and Hottinger (2013). This paper is one of the chapters from a new book that is being prepared by the first author, entitled Pioneers and Milestones of Indonesian Geology ( 1820-1960).